Induction of Immune Tolerance to a Therapeutic Protein by Intrathymic Gene Delivery - Chu, Qiuming (Nature Publishing Group, 2010)
The efficacy of recombinant enzyme therapy for genetic diseases is limited in some patients by the generation of a humoral immune response to the therapeutic protein. Inducing immune tolerance to the protein prior to treatment has the potential to increase therapeutic efficacy. Using an AAV8 vector encoding human acid α-glucosidase (hGAA), we have evaluated direct intrathymic injection for inducing tolerance. We have also compared the final tolerogenic states achieved by intrathymic and intravenous injection. Intrathymic vector delivery induced tolerance equivalent to that generated by intravenous delivery, but at a 25-fold lower dose, the thymic hGAA expression level was 10,000-fold lower than the liver expression necessary for systemic tolerance induction. Splenic regulatory T cells (Tregs) were apparent after delivery by both routes, but with different phenotypes. Intrathymic delivery resulted in Tregs with higher FoxP3, TGFβ, and IL-10 mRNA levels. These differences may account for the differences noted in splenic T cells, where only intravenous delivery appeared to inhibit their activation. Our results imply that different mechanisms may be operating to generate immune tolerance by intrathymic and intravenous delivery of an AAV vector, and suggest that the intrathymic route may hold promise for decreasing the humoral immune response to therapeutic proteins in genetic disease indications.